In the footsteps of Bob and Angelina: Celebrities’ diverse societal engagement and its ability to attract media coverage - Panis, Koen and Van den Bulck, Hilde (Communications, 2014)
Abstract While media coverage is a main aim of celebrities’ societal engagement, academic analysis of its news-making ability is scarce. As a diverse phenomenon, we argue that the ability of celebrities’ societal engagement to attract media attention depends on how certain characteristics (i.e., celebrities’ claim to fame, roles they take on and issues they support) fit news selection criteria to a greater or lesser extent. First, this article determines how the three studied components (claim to fame, role and issue) relate to each other by means of an internet search and analysis. Second, using the internet data as a benchmark, the article looks at how celebrities’ engagement is covered in Flemish newspapers. Results suggest that certain forms of celebrities’ societal engagement are more likely than others to generate media coverage, as Flemish newspapers tend to focus more on the issue of development aid, ad hoc celebrity roles, and local Flemish celebrities and issues.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTUxNS9jb21tdW4tMjAxNC0wMDAz